The SAPUVETNET Projects: experiences of intersectoral collaboration and research/training in Veterinary Public Health across Latin America and Europe. - De Meneghi, Daniele (2012)
SAPUVETNET is the acronym of “Red de Salud Publica Veterinaria/Network of Veterinary Public Health”, a series of projects co-financed under the EU ALFA program, aimed to support an International network on Veterinary Public Health (VPH) constituted by Faculties of Veterinary Medicine from Latin-America (LA) and Europe (EU) (http://www.sapuvetnet.org). Since its start in 2002, SAPUVETNET has been continuously growing and expanding, and now it also includes several International collaborating institutions/organizations. The SAPUVETNET projects have envisaged a series of objectives/activities aimed to promote and enhance VPH research/training and intersectoral collaboration across LA and EU. Project partners use a mail-list and distance learning platforms (e.g. Moodle, Colibri) to organize common teaching activities. Major results so far achieved are: harmonisation/development of a common VPH curriculum; creation of common modules/courses on selected VPH topics; use of innovative teaching methods, based on problem solving approach/case studies; publication of videos (DVDs) and self-learning program (CD-ROM) on meat inspection/hygiene (in 3 languages); development of an on-line VPH teaching Manual (beta version in Spanish); organization of e-conferences on upcoming VPH issues; publication of a new International VPH Journal “Una Salud/One Health/Uma Saude” (in 3 languages); exchanges of teachers/researchers (e.g. bilateral visits LA-EU-LA) and coordinating meetings; participation in and/or organization of VPH seminars/congresses/conferences at National and International level; publication of scientific and popular articles on VPH issues related to project activities. SAPUVETNET didactic tools have been and/or are being tested/used by partner faculties/universities and other teaching institutions. Didactic material can be freely circulated and distributed, and can be used for distance learning, be modified/adapted to the local context of any country/geographical area, even outside LA and EU.